2007
DOI: 10.1111/j.1524-475x.2007.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute complex traumas of the lower limbs: a modern reconstructive approach with negative pressure therapy

Abstract: Acute traumas of the lower limbs cause complex functional damage for the association of skin loss with exposed tendons, bones, and/or vessels, requiring a multidisciplinary approach. Once bone fixation and vascular repair have been carried out, the surgical treatment for skin damage is usually based on early coverage with conventional or microsurgical flaps. Negative pressure therapy can play a primary role in the management of the elderly or intensive care patients, where wounds are secondary to life-threaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Several publications report on the benefits of NPWT as an advanced means of wound bed preparation in wounds with exposed bone [3,21,[26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Several publications report on the benefits of NPWT as an advanced means of wound bed preparation in wounds with exposed bone [3,21,[26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research asserts that many MMPs have overlapping functions [16]. A thorough literature search has revealed that the major MMPs involved in wound remodeling are MMPs 1,2,3,7,8,9,10,12, and 13, although, with ongoing research, it is likely that all MMPs play essential roles in wound healing. [13,14,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Negative-pressure vacuum-assisted closure device (VAC) usage, in combination with serial debridements of devitalized tissue and high-pressure wound irrigation, has greatly reduced the morbidity of such traumatic extremity wounds [9,10]. Although these methods have been accepted as the standard of care in many institutions, timing of surgical closure of a wound remains a subjective process in which the surgeon relies on criteria such as the patient's overall condition, wound location, wound bed gross appearance, and local perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bollero et al 14 reported on the use of NPWT/ ROCF for management of complex traumatic soft-tissue wounds in patients for whom immediate flap coverage was desirable but relatively contraindicated because of multisystem trauma or significant medical comorbidities. They reported success with achieving soft-tissue coverage in this population and concluded that use of NPWT/ROCF represented a valid alternative to traditional rotational or free tissue coverage in this challenging population.…”
Section: Traumatic Woundsmentioning
confidence: 97%